Public Firm Size Moderating Factors on Audit Report Lag: Evidence from ASEAN - Tanggor Sihombing; Natasya Florencia (Universitas Pendidikan Indonesia, 2024)
This research aimed to examine the effect of audit tenure, financial distress, and solvency on audit report lag while considering the size of public firm size as a moderating factor. By employing purposive sampling method, samples of 135 companies from the real estate industry in the Big 5 ASEAN that are listed on SandP Capital IQ from the period 2020-2022 are gathered. This research employs a quantitative approach and data will be analyzed using STATA ver. 17. The research findings demonstrated that audit tenure has a negative effect on audit report lag, whereas financial distress and solvency have a positive impact. The public firm size does not significantly strengthen the negative effect of audit tenure and does not significantly weaken the positive effect of financial distress on audit report lag. However, the public firm size can strengthen the positive effect of solvency on audit report lag. This research aims to provide theoretical implications whereas audit tenure affects agency theory while financial distress and solvency affect compliance theory. While practical implications suggest that companies engage the same auditor, monitoring financial conditions and solvency levels to reduce audit report lags. The novelty of this research is by using real estate industry companies located in the Big 5 ASEAN countries (Indonesia, Thailand, Singapore, Malaysia, and Vietnam) as the population and thus enriching understanding within this specific context and extending the applicability of findings to this sector.